Exploring Some Aspects Associated with Dentine Hypersensitivity in Children - Caleb Shitsuka; Fausto Medeiros Mendes; Maria Salete Nahás Pires Corrêa; Mariana Ferreira Leite (The Scientific World Journal, 2015)
Background. The etiology of dentine hypersensitivity (DH) is still inconclusive and there are few studies concerning it in children. Aim. To evaluate clinical, dietary, and salivary variables in children with DH complaints. Design. Forty-eight children were asked about DH. Data regarding dietary habits were collected from the children’s parents and an examination was performed to determine dental erosion. Dental biofilm was estimated by oral hygiene status, according to Greene and Vermillion’s Simplified Oral Hygiene Index (OHI-S). Whole saliva was collected under mechanical stimulation and evaluated salivary flow rate, initial pH, buffer capacity, and calcium and phosphate concentrations. The temperature of soft drinks, drinking method, sense of bitter taste, and other variables were also determined. Possible factors associated with DH were analyzed by univariate and multiple Poisson regression analyses. The prevalence ratio (PR) values and 95% confidence intervals (95% CI) were calculated. Results. DH was associated with the presence of dental erosion (PR; 95% CI = 2.23; 1.05 to 4.71) and salivary flow rate (2.49; 1.05 to 5.91). When the presence of erosion was not included, other variables were retained as follows: bitter taste (2.36; 1.38 to 4.03), OHI-S (0.47; 0.23 to 0.97). Conclusion. DH in children is associated with factors related to dental erosion.